Vote buying in the US Congress - Ulrich Matter; Paolo Roberti; Michaela Slotwinski (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
We assess the influence of moneyed interests on legislative decisions. Our theory predicts that the vote outcome distribution and donation flows in a legislature feature a discontinuity at the approval threshold of bills if special interest groups are involved in vote buying. Testing the theoretical predictions based on two decades of roll-call voting in the U.S. House, we identify the link between narrowly passed bills and well-timed campaign contributions. Several pieces of evidence substantiate our main finding, suggesting that moneyed interests exert remarkably effective control over the passage of contested bills.
Keywords: D72; D78; 330; legislative voting; campaign finance; special interest groups; lobbying; forensic economics